PENGARUH CELEBRITY ENDORSER, DAYA TARIK IKLAN, DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN DI E-COMMERCE SHOPEE (STUDI KASUS PADA PENGGUNA E-COMMERCE SHOPEE DI UNIVERSITAS MAYJEN SUNGKONO MOJOKERTO) - Avifah Nihmatus Solikhah; Indra Krishernawan (Pusat Riset dan Inovasi Nasional, 2022)
Rapid technological advancements, coupled with the establishment of e-commerce businesses in Indonesia, resulted in the emergence of a new marketing phenomenon or event, namely online marketing. The primary goal of this research was to ascertain the effect of advertising appeal, celebrity endorser, and online word of mouth on Shopee e-commerce purchase decisions (Shopee e-commerce user case study, Mojokerto, Mayjen Sungkono University).Non-probability sampling and target sampling are two sampling techniques. Mayjen Sungkono Mojokerto, a college student who used Shopee, participated in the study by providing 100 responses. To collect data, Likert surveys were used. Multiple linear model was used to assess the data in this study, as well as a rability test, a validity test a hypotesis test, and a classical hypothesis test. According to the test results, celebrity speakers, advertising attractiveness, and e-WOM all have a statistically significant positive effect on variable purchase decisions. Simultaneous regression analysis (test f) demonstrates that all examined uncorrelated (free) variables have a statistically significant impact on correlated (bound) purchase decisions.